1981
DOI: 10.1113/jphysiol.1981.sp013697
|View full text |Cite
|
Sign up to set email alerts
|

Diminished response to beta‐bungarotoxin in neonatal rat diaphragm.

Abstract: SUMMARY1. The effects of fl-bungarotoxin on acetylcholine turnover were studied in neonatal rat diaphragms using a gas chromatographic mass spectrometric assay to measure acetylcholine and choline.2. Injection of neonatal rats (1-15 days old) with a fixed dose of fl-bungarotoxin resulted in a shorter time to death in the older animals.3. This increased lethal potency of fl-bungarotoxin in the older rats was correlated with an enhancement of the stimulatory effect of the toxin on acetylcholine synthesis in diap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The toxin has a high affinity and saturable binding capcity toward isolated brain membranes of rat (Oberg and Kelly, 1976) and chick (Rehm and Betz, 1982). It reduces the levels of amino acid neurotransmitters in brain synaptosomes (Wernicke et al, 1974;Smith et al, 1980), but stimulates the synthesis and accumulation of acetylcholine (ACh) in rat phrenic nerve (Gundersen, 1981; Gundersen et al, 1981). It has also been demonstrated that 6-BT inhibits the high-affinity choline (Ch) transport in Torpedo electric organ (Dowdall et al, 1977).…”
mentioning
confidence: 99%
“…The toxin has a high affinity and saturable binding capcity toward isolated brain membranes of rat (Oberg and Kelly, 1976) and chick (Rehm and Betz, 1982). It reduces the levels of amino acid neurotransmitters in brain synaptosomes (Wernicke et al, 1974;Smith et al, 1980), but stimulates the synthesis and accumulation of acetylcholine (ACh) in rat phrenic nerve (Gundersen, 1981; Gundersen et al, 1981). It has also been demonstrated that 6-BT inhibits the high-affinity choline (Ch) transport in Torpedo electric organ (Dowdall et al, 1977).…”
mentioning
confidence: 99%